Evaluación de la planta de tratamiento de agua potable de la parroquia Bellamaría del cantón Santa Rosa. - Romero Jaramillo, Bryan Andrés (My University, 2022)
This work is based on the technical evaluation of the drinking water treatment plant of the Bellamaría parish in the Santa Rosa city. The DWTP presents different operational problems such as the clogging of its SSF, so we proceeded to make an evaluation of the DWTP obtaining 3 water samples, 3 visits to the DWTP were made resulting in the preparation of a sketch of the plant and a visual inspection of the status and operation of each unit. A survey of the information of the beneficiary users of the service was carried out, obtaining 444 connections. Based on the average water supply and the population estimate, a required flow rate of 4.76 l/s was determined, exceeding the design flow rate. When evaluating the DWTP it was found that the DCF is not operating, the raw water is conducted through two PVC pipes of 100 mm and 75 mm that arrive directly to the distribution box, omitting the pre-filter. The SSFs do not operate at the same time; one SSF operates until it stops filtering the water and then the operator switches to the second SSF, causing the filtered water to not meet the parameters established in the standard. Bacteriological analyses show the presence of fecal coliforms in the household water. In the physicochemical analysis of the raw and treated water, the apparent color and turbidity parameters showed values higher than the limits allowed by NTE INEN 1108, a problem caused by very high filtration rates. .
El presente trabajo está basado en la evaluación técnica de la planta de tratamiento de agua potable de la parroquia Bellamaría en el cantón Santa Rosa. La PTAP presenta diferentes problemas de funcionamiento como la colmatación de sus FLA por lo que se procedió hacer una evaluación de la PTAP obteniendo 3 muestras de agua, se realizaron 3 visitas a la PTAP dando como resultado la elaboración de un croquis de la planta y una inspección visual del estado y funcionamiento de cada unidad. Se hizo un levantamiento de información de los usuarios beneficiarios del servicio obteniendo 444 conexiones, en función de la dotación media y la estimación de población se determinó un caudal requerido de 4.76 l/s superando el caudal de diseño. Al evaluar la PTAP se encontró que el FGDi no está operando, el agua cruda es conducida por 2 tuberías PVC de 100 mm y 75 mm que llegan directo al cajón distribuidor omitiendo el pre-filtro. Los FLA no operan al mismo tiempo, funciona un FLA hasta que deje de filtrar el agua y luego el operador cambia al segundo FLA provocando que el agua filtrada no cumpla con los parámetros establecidos en la norma. Los análisis bacteriológicos demuestran la presencia de coliformes fecales en el agua de domicilio. En los análisis físico-químicos del agua cruda y tratada los parámetros de color aparente y turbiedad arrojaron valores mayores a los límites permitidos en la NTE INEN 1108, problemática causada por tasas de filtración muy altas.
Keywords: FGDI; FIME; LECHO FILTRANTE; AGUA POTABLE; ZONA RURAL; PLANTA DE TRATAMIENTO